PERAN PENTING HOUSEKEEPING DEPARTMENT BAGIAN ROOM DAN LAUNDRY DI HOTEL IBIS MALIOBORO YOGYAKARTA - , INDRA KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Room and Laundry are two parts which be related and they have important task and role especially in housekeeping department so that to be a tip of spear in a hotel. So in this Last Task will be explain about their task and role which called important component of hotel. Needed a recent survey to understanding those thing so that the explanattion will be write down doesnât lost of meaning. In this case on the job training and recent interview by profesional staff in Hotel Ibis Malioboro Yogyakarta is better method to used. This research produce many profit which very important for room and laundry, the one of all is helping housekeeping department to keep hotel image stay good and handle service.